Metrology of Platinum Nanozymes: Mechanistic Insights and Analytical Issues - Cursi, Lorenzo; Mirra, Giulia; Boselli, Luca; Pompa, Pier Paolo (Advanced functional materials, 2024)
Thanks to their properties, stability, and multifunctionality, nanozymes are increasingly impacting several fields, including medicine, diagnostics, and environmental science. However, clear information about their catalytic properties and mechanisms is still lacking. Several critical issues are currently under discussions, such as the absence of univocally accepted catalytic mechanisms, standardized protocols for directly comparing nanozymes versus enzymes, and a comprehensive characterization of their performance in different chemical/biological environments. All these issues strongly limit the advancement of the field. Herein, nanozymes metrology and analysis of both catalytic mechanisms and methodological procedures are attempted, taking platinum nanozymes as a case study thanks to their multifunctional catalytic features. The oxidoreductase activities of Pt‐nanozymes (i.e., peroxidase‐, oxidase‐, and catalase‐like reactions) are critically investigated in different physical/chemical environments, clarifying fundamental aspects and providing general methodological guidelines for nanozyme properties characterization. Furthermore, PtNP activities are compared with natural enzymes in different conditions, and their performance and catalytic behavior are evaluated by calculating the turnover frequency (TOF) with different normalization strategies. The results highlight that Pt‐nanozymes are efficient catalysts, exhibiting outstanding catalase‐like activity. This work clarifies several key points concerning Pt‐nanozyme properties and general metrological issues, providing a workflow that can become a reference for several nanozymes characterizations. The multi‐enzymatic activity of platinum nanozymes is investigated, providing insights into their catalytic mechanisms. Their oxidoreductase activities are investigated as a function of pH and temperature, tackling analytical issues related to the use of chromogenic probes and buffers. PtNP activities are compared with natural enzymes, evaluating their performance and catalytic behavior.